Penerapan Strategi Pembelajaran Efektif oleh Guru PAI dalam Meningkatkan Motivasi Belajar Siswa - Anjir Faghnawy Achmada; Muhammad Assyauqi Zam Zami; Moh Syafiqur Romzi; Rofiatul Hosna (Universitas Islam Lamongan, 2025)
The purpose of this study is to analyze and describe motivation theories, learning motivation from an Islamic perspective, and teachers’ strategies in creating effective learning. This study employs a qualitative method with a literature review approach. The findings show that various motivation theories have been developed, including Maslow’s hierarchy of needs, Herzberg’s two-factor theory, McClelland’s need for achievement theory, McGregor’s Theory X and Theory Y, and Vroom’s expectancy theory. Learning is an obligation for every Muslim, as emphasized in the Qur’an and Hadith. Learning activities are not only of academic value but also serve as acts of worship and means of drawing closer to Allah. Teachers’ strategies to enhance learning motivation include instilling awareness of the obligation to seek knowledge, encouraging students to develop enthusiasm for learning, considering spiritual and internal factors that influence motivation, and integrating Islamic values into the learning process. Thus, learning becomes more meaningful, effective, and capable of shaping students’ religious character.